2021
DOI: 10.1186/s12245-021-00369-2
|View full text |Cite
|
Sign up to set email alerts
|

A young woman presented with massive pulmonary embolism with inferior vena cava thrombus as a complication of nephrotic syndrome: a case report

Abstract: Nephrotic syndrome (NS) was first described in 1827 as the presence of proteinuria of ≥ 3.5 g/24 h, hypoalbuminemia < 3.0 g/dl, peripheral edema, hyperlipidemia, lipiduria, and increased thrombotic risk. Nephrotic syndrome has an incidence of three cases per 100,000 each year in adults. Nephrotic syndrome also has serious complications due to hypercoagulable state in both various venous and arteries which could lead thromboembolic events. The pathophysiology of hypercoagulability in the nephrotic syndrome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…NS was first characterized in 1827 as the occurrence of proteinuria greater than or equal to 3.5 g/24 h, hypoalbuminemia (albumin≤3.0 g/dl), peripheral edema, hyperlipidemia, lipiduria caused by increased permeability of the renal glomerulus 1 , 2 . The estimated population incidence of NS is roughly 3 per 100 000 people per year 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS was first characterized in 1827 as the occurrence of proteinuria greater than or equal to 3.5 g/24 h, hypoalbuminemia (albumin≤3.0 g/dl), peripheral edema, hyperlipidemia, lipiduria caused by increased permeability of the renal glomerulus 1 , 2 . The estimated population incidence of NS is roughly 3 per 100 000 people per year 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The estimated population incidence of NS is roughly 3 per 100 000 people per year 3 . The increased permeability of the glomerulus can be due to primary causes which include focal segmental glomerulosclerosis, membranous nephropathy, and minimal change disease, and secondary causes which comprise of diabetes, systemic lupus erythematosus, multiple myeloma, amyloidosis, and infections 1 . Although, albumin is the major protein that will be lost in the urine in the case of NS, some other binding proteins like thyroxine-binding globulin and transthyretin, and thyroid hormones itself will be lost resulting in hypothyroidism 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by impairment in glomerular permeability, which may be due primarily to intrinsic renal pathology or secondarily to various causes such as congenital causes, infections, diabetes, systemic lupus erythematous, neoplasia, or the use of drugs 2 . It has been observed that VTE including pulmonary embolism, deep venous thrombosis, renal vein thrombosis, and inferior vena cava thrombosis are the most common life-threatening complications of NS 3 . PVT is thrombosis that occurs in the body of the portal vein and also its right and left intrahepatic branches and may spread to the splenic or superior mesenteric veins.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated population incidence of NS is roughly 3 per 100,000 people per year (2). The increased permeability of the glomerulus can be due to primary causes which include focal segmental glomerulosclerosis (FSGS), membranous nephropathy (MN), and minimal change disease (MCD), and secondary causes which comprise of diabetes, systemic lupus erythematous, multiple myeloma, amyloidosis, and infections (1).…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotic syndrome (NS) was rst characterized in 1827 as the occurrence of proteinuria greater than or equal to 3.5 g/24 hours, hypoalbuminemia (albumin less than or equal to 3.0 g/dl), peripheral edema, hyperlipidemia, lipiduria caused by increased permeability of the renal glomerulus (1). The estimated population incidence of NS is roughly 3 per 100,000 people per year (2).…”
Section: Introductionmentioning
confidence: 99%